R&D as a prisoner’s dilemma and R&D - avoiding cartels - Rabah, Amir (2011)
Duopoly firms engaged in a standard two-stage game of R&D and Cournot competition are caught in a prisoner’s dilemma for their R&D decisions whenever spillover effects are low. This effect works to the advantage of consumers and society. This result provides an interesting perspective on the well-known wedge between private and social incentives for R&D. The prisoner’s dilemma is the key effect behind this wedge under low spillovers. The latter take over when sufficiently high, as is widely recognized. This mutually exclusive nature of the prisoner’s dilemma and significant spillovers also serves to explain the incentives to form R&D cartels.